Manajemen dan Pencatatan Ternak Berbasis Internet Of Things Pada Program Penggemukan Kambing - Amaliatus Sholicha, Nanda; Randali Irfandi; Carles Turawan (Departemen Ilmu Komputer, Institut Pertanian Bogor, 2023)
Indonesia has great potential in the agrarian sector, especially livestock. This potential can be seen in the goat commodity whose market demand always grows exponentially. Facts on the ground in Indonesia found several weaknesses in the management system for goat livestock data collection or recording. Livestock registration in Indonesia still applies conventional methods with individual ownership using paper, not using RFID, there is no control and monitoring of cage conditions which will affect livestock growth if the conditions of the cage are unstable, and have not implemented schedules and reports. feeding. The purpose of this research is to create an IoT-based electronic recording idea with a mobile system to simplify the livestock recording process. The method used is the IoT method which includes the stages: analysis, design, implementation and testing. The Smart Goat application has several features, namely livestock data management, composition and feeding, monitoring of temperature and light intensity, humidity, ammonia gas, monitoring of body weight and temperature control. The advantages of Smart Goat are that the application can be accessed from anywhere and at any time via the internet, this system is also equipped with an RFID sensor, digital scales, and controllers and monitors, sometimes integrated with servers. This makes the updated data in the system complete, fast, precise, and accurate.Keywords: Goat Fattening, Internet of Things, and Recording